Relationship between teacher’s personality, monitoring, learning environment, and students’ EFL performance - Nik Mohd Hazrul Nik Hashim; Syed Shah Alam; Norazlina Mohd Yusoff (Penerbit UKM, 2014)
Teachers have been widely acknowledged to critically influence students‘ learning and achievement. Nonetheless, the effects of teacher characteristics on student communication proficiency in the context of English as foreign language (EFL) learning have not received adequate attention among scholars. In contrast to most studies in the area, this article focuses on the influence of teacher-student interpersonal engagements, namely teacher‘s personality and monitoring, on EFL student communication proficiency. The purpose of this study is to explore whether teacher‘s characteristics and environmental learning factors influence students‘ overall communication proficiency. Drawing on sociocultural theory, the authors assume that EFL learning is bi-directional in nature. In addition to conceptualizing the direct impact of domain-specific determinants of communication proficiency, internal classroom conditions and external college facilities were assessed for possible moderating effects. Using a sample of college students in twelve different campus locations from Institut Kemahiran Mara (IKM), across Malaysia, the authors performed a regression analysis to empirically test the proposed research hypotheses. All constructs demonstrated low levels of multicollinearity and measurement scales indicated sufficient reliability and validity. Results show that teacher‘s personality is an important determinant of student proficiency in English. Monitoring efforts, however, did not have a direct influence on English proficiency but coupled with teacher‘s personality and college facilities, respectively, the coefficient interaction effects became significant. The results also reveal that classroom conditions do not interact with teacher‘s personality to improve student learning outcomes, nonetheless acts more predominantly as a predictor that directly enhances students‘ learning. Important research implications and future research directions are suggested.